9(2r-1)=8(4r+12)

Simple and best practice solution for 9(2r-1)=8(4r+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2r-1)=8(4r+12) equation:


Simplifying
9(2r + -1) = 8(4r + 12)

Reorder the terms:
9(-1 + 2r) = 8(4r + 12)
(-1 * 9 + 2r * 9) = 8(4r + 12)
(-9 + 18r) = 8(4r + 12)

Reorder the terms:
-9 + 18r = 8(12 + 4r)
-9 + 18r = (12 * 8 + 4r * 8)
-9 + 18r = (96 + 32r)

Solving
-9 + 18r = 96 + 32r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-32r' to each side of the equation.
-9 + 18r + -32r = 96 + 32r + -32r

Combine like terms: 18r + -32r = -14r
-9 + -14r = 96 + 32r + -32r

Combine like terms: 32r + -32r = 0
-9 + -14r = 96 + 0
-9 + -14r = 96

Add '9' to each side of the equation.
-9 + 9 + -14r = 96 + 9

Combine like terms: -9 + 9 = 0
0 + -14r = 96 + 9
-14r = 96 + 9

Combine like terms: 96 + 9 = 105
-14r = 105

Divide each side by '-14'.
r = -7.5

Simplifying
r = -7.5

See similar equations:

| 2n^2-32n+128= | | 3x+1+19=10 | | x+(x+39)+(2x-40)=699 | | 5xy=2 | | 2x^2-4=2 | | 2x^2+14x=36 | | 9x^2-62x-80=0 | | -2x(x-4)=4 | | 5(t-6)+7t=4(3t+5)-10 | | 3x^2+15x=150 | | 15(t-6)+6t=7(3t+3)-10 | | 5(t-6)+7t=5(3t+5)-10 | | 50+60x=80+50x | | -5v+6=0 | | 36b^2-25=0 | | y+7.4=3.6 | | v-5v+6=0 | | -6+(-4d)=-14 | | 5(6a-8)-9a=7-5 | | x-8.8=3.1 | | 5a+8-4a=1 | | -13+12p=11 | | X=49 | | -13+12p= | | v^2+4v-32=0 | | -2(x-3)+3x=2-5 | | 4x^2+13x+9=x | | 16x^2-160=48x | | 15x-23=2x+5-x | | 8-11=a-9 | | (3x+5)(2x^2-9x-9)=0 | | 34+y=3(8+y) |

Equations solver categories